External radiation exposure and mortality in a cohort of French nuclear workers. Issue 10 (23rd May 2007) - Telle-Lamberton, M; Samson, E; Caër, S; Bergot, D; Bard, D; Bermann, F; MGélas, J; Giraud, J M; Hubert, P; Metz-Flamant, C; Néron, M O; Quesne, B; et al.
Abstract : Objective: To analyse the effect of external radiation exposure on the mortality of French nuclear workers. Methods: A cohort of 29 204 workers employed between 1950 and 1994 at the French Atomic Energy Commission (Commissariat à l'Energie Atomique (CEA)) or at the General Company of Nuclear Fuel (COmpagnie GEnérale des MAtières nucléaires (Cogema, now Areva NC)) was followed up for an average of 17.8 years. Standardised mortality ratios (SMRs) were computed with reference to French mortality rates. Dose-effect relationship were analysed through trend tests and Poisson regression, with linear and log-linear models. Results: The mean exposure to X and gamma radiation was 8.3 mSv (16.9 mSv for exposed worker population). A total of 1842 deaths occurred between 1968 and 1994. A healthy worker effect was observed, the number of deaths in the cohort being 59% of the number expected from national mortality statistics. Among the 21 main cancer sites studied, a statistically significant excess was observed only for skin melanoma, and an excess of borderline statistical significance was observed for multiple myeloma. A dose-effect relationship was observed for leukaemia after exclusion of chronic lymphoid leukaemia (CLL). The relative risk observed for non-CLL leukaemia, n = 20, was 4.1 per 100 mSv (90% CI 1.4 to 12.2), linear model and 2.2 per 100 mSv (90% CI 1.2 to 3.3), log-linear model. Significant dose-effect relationship were also observed for causes of deaths associated with alcohol consumption: mouth and pharynx cancer, cirrhosis and alcoholic psychosis and external causes of death. Conclusion: The risk of leukaemia increases with increasing exposure to external radiation; this is consistent with published results on other nuclear workers cohorts.